2020
DOI: 10.1007/s10956-020-09816-w
|View full text |Cite
|
Sign up to set email alerts
|

Using Smartphones as Experimental Tools—a Follow-up: Cognitive Effects by Video Analysis and Reduction of Cognitive Load by Multiple Representations

Abstract: Mobile devices (smartphones or tablets) as experimental tools (METs) offer inspiring possibilities for science education, but until now, there has been little research studying this approach. Previous research indicated that METs have positive effects on students' interest and curiosity. The present investigation focuses on potential cognitive effects of METs using video analyses on tablets to investigate pendulum movements and an instruction that has been used before to study effects of smartphones' accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 54 publications
2
27
0
2
Order By: Relevance
“…The learner thus has more free cognitive resources available for active knowledge construction, which increases the effectiveness of the learning process and ultimately leads to a deeper conceptual understanding. This supports the theoretical foundation of effectiveness of tablet-based video analysis derived from multimedia learning theories and contributes to an expansion of the research basis by providing a possible explanation for the positive effects on learning achievement already proven in several studies (Becker et al 2018(Becker et al , 2019Hochberg et al 2020;Klein et al 2018). Furthermore, it could also be shown that basic theoretical design principles for multimedia learning environments can also have a learning-promoting effect in real multirepresentational teaching scenarios.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The learner thus has more free cognitive resources available for active knowledge construction, which increases the effectiveness of the learning process and ultimately leads to a deeper conceptual understanding. This supports the theoretical foundation of effectiveness of tablet-based video analysis derived from multimedia learning theories and contributes to an expansion of the research basis by providing a possible explanation for the positive effects on learning achievement already proven in several studies (Becker et al 2018(Becker et al , 2019Hochberg et al 2020;Klein et al 2018). Furthermore, it could also be shown that basic theoretical design principles for multimedia learning environments can also have a learning-promoting effect in real multirepresentational teaching scenarios.…”
Section: Resultssupporting
confidence: 80%
“…Due to the increasing use of mobile technologies both in everyday life and in the education sector, Mutlu-Bayraktar et al (2019) recommend that the influence of mobile technologies on cognitive load in teaching-learning situations should also be systematically investigated in empirical studies. In this respect, initial studies have shown positive effects of using mobile devices to enhance inquiry-based experimental learning with multiple representations on conceptual understanding (e.g., Becker et al 2018Becker et al , 2019Becker et al , 2020Klein et al 2018;Kuhn and Vogt 2015;Hochberg et al 2020) and motivation (e.g., Hochberg et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since passive blocking does not involve active signal jamming, it will not require Federal Communications Commission (FCC) approval (in case jamming is preferred permission must be obtained from the FCC). The professor must be given access to a switch to turn on wifi when it is time to conduct some high technology higher learning activity that makes use of the internet or other smart phone experiment (Hochberg et al 2020 ). The wifi can be turned off after the internet exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Line graphs, in particular, are frequently used in higher education. For example, the relationships between distance and speed in physics or between time and stock prices in finance can both be illustrated with a line graph ( Bowen and Roth, 1998 ; Benedict and Hoag, 2012 ; Susac et al, 2018 ; Becker et al, 2020a , b ; Hochberg et al, 2020 ; Klein et al, 2020 ). More recently, a number of studies investigated and compared university students’ understanding of graphs in mathematics, physics, and other contexts using parallel (isomorphic) tasks ( Christensen and Thompson, 2012 ; Planinic et al, 2012 , 2013 ; Wemyss and van Kampen, 2013 ; Bollen et al, 2016 ; Ivanjek et al, 2016 , 2017 ).…”
Section: Research Focus and Objectivementioning
confidence: 99%
“…However, there are currently only few studies with a pretest–posttest assessment design focusing on the changes in graph understanding and how to foster this understanding. Digital learning environments, learning from examples, and using instructional material showed an impact on students’ graph comprehension ( Bell and Janvier, 1981 ; Bergey et al, 2015 ; Becker et al, 2020a , b ; Hochberg et al, 2020 ). For example, the impact of instruction on graph construction conventions (e.g., on legends and labels) on students’ graph understanding was confirmed in a control group design ( Miller et al, 2016 ).…”
Section: Background Of the Post-replication Studymentioning
confidence: 99%